Anthropometric measurements of ankle mortise for evaluating mortise fracture reductions with an aim to develop contoured implants - M.S. Patil; S.M.G. Raza; Md. Nayeem Ali (Al Ameen Medical College, 2012)
Background: Ankle injuries are unique as they are not only intra-articular of weight bearing joint, but also caused by a variety of mechanism, each resulting in different pattern with ankle fractures. The primary concern is residual instability of the joint as malalignment or residual displacement can adversely affect the biomechanical behaviour of ankle and resulting loss of function, due to non restoration of normal anatomy. Therefore essential of proper anatomical parameters for assessment of reduction and improved designs of implants used to get good results. Objectives: Measuring various radiological and Anatomical normal parameters of the ankle mortise. Material and Methods: Cadaveric 20 fibula and 27 tibia. Anteroposterior and 15○ internal rotation radiographs, of both Ankles in 20 adult individuals formed the material. Following parameters measured- a) Tibiofibular clearspace b) Tibiofibular overlap c) Talocrural angle d) Length of medial and lateral malleoli e) Angles sustained on medial surface of medial malleoli and lateral surface of lateral malleoli. Results: a) Tibiofibular clear space on Anteroposterior 2.4mm (±1.3mm) in 15○ rotation 4.5mm (±1.2mm). b) Tibiofibular overlap in Anteroposterior 11.2mm (±4.4mm) in 15○ rotation 4.2mm (±1.7mm). c) Talocrural angle in Anteroposterior 77.7mm (±3.2mm) in 15○ rotation 79.9mm (±2.9mm). d) Length of medial malleolus in Anteroposterior 15.3mm (±1.01mm) in 15○ rotation 15.3mm (±0.8mm). e) Length of lateral malleolus in Anteroposterior 27.35mm (±3.8mm) in 15○ rotation 26.5mm (±5.1mm). Angles- Lateral bend of lateral malleolus was ranging 8○-21○ average being 16.2○. Medial bend of medial malleolus was ranging 10○-34○, average 19.5○. Conclusion: The unique measurement of angles on both surface of malleoli and other parameters definitely contribute for assessment of reduction and prognostic evaluations of ankle fracture, Designing, moulding and manufacturing of prebent plates for use in distal ends of tibia and fibula.